(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Neonatal intestinal obstruction is a common surgical emergency with significant morbidity and mortality. Prematurity and low birth weight are recognized risk factors for adverse postoperative outcomes, but their specific impact in this context requires further evaluation. Objective: To assess the impact of prematurity and low birth weight on postoperative mortality in neonates undergoing surgery for intestinal obstruction.Methods: This prospective observational study was conducted in the Department of Pediatric Surgery, Sylhet M.A.G. Osmani Medical College Hospital, from December 2017 to November 2019. A total of 108 neonates with intestinal obstruction who underwent surgical intervention were enrolled using purposive sampling. Data were analyzed with SPSS version 25.Results: Among 108 neonates, 47.2% were preterm and 52.8% were term. Low birth weight (<2500g) was observed in 54.63% of patients, including 15.75% very low birth weight. Anorectal malformation (22.3%), Hirschsprung’s disease (19.5%), and intestinal atresia (18.5%) were the most common diagnoses. Overall mortality was 13% (14 patients). Preterm neonates had significantly higher mortality (17.6%) compared to term neonates (8.6%). The mean birth weight of survivors (2.6 kg) was higher than that of non-survivors (1.9 kg). Mortality was highest in volvulus (25%), necrotizing enterocolitis (25%), and intestinal atresia (20%). Septicemia (25%) was the leading cause of death. Conclusion: Prematurity and low birth weight are significant risk factors for postoperative mortality in neonatal intestinal obstruction. Preterm and low birth weight neonates require intensive perioperative care and close monitoring to improve survival outcomes. Journal of Paediatric Surgeons of Bangladesh (2023) Vol. 14 (1 & 2): 4-10